Public-Private Partnership for Eco-Tourism Development: A Bibliometric Review of Collaborative Frameworks - Judijanto, Loso (West Science Social and Humanities Studies, 2025)
This study presents a comprehensive bibliometric review of scholarly research on Public-Private Partnerships (PPPs) for eco-tourism development, with the aim of mapping the collaborative frameworks, research themes, and global trends that have shaped the field over the past two decades. Using data extracted from the Scopus database and analyzed through VOSviewer software, the study identifies key concepts, author and institutional networks, and geographic contributions that have influenced discourse on sustainable tourism partnerships. The co-occurrence analysis reveals dominant themes such as sustainable development, governance, tourism management, risk assessment, and environmental protection, while temporal overlay mapping highlights a shift from foundational governance-oriented studies to more recent emphases on innovation, investment, and climate resilience. Country collaboration networks underscore the central role of nations like the United States, United Kingdom, China, and Australia, while also pointing to underrepresentation in certain regions. The findings offer both practical insights for policymakers and private stakeholders in designing inclusive, efficient PPP frameworks, and theoretical contributions by highlighting evolving research clusters and interdisciplinary gaps. This study serves as a foundation for future inquiry and global collaboration in sustainable eco-tourism governance.